Youth Leadership Mentoring Based on Islamic and Muhammadiyah Values at the Budi Mulia Social Institution Jember as a Smart Social Care Leadership Model - Akbar Maulana; Sudahri Sudahri (Journal Of Humanities Community Empowerment, 2026)
This community service program aims to develop and implement the Leadership Smart Social Care model based on Islamic and Muhammadiyah values in strengthening youth leadership at Panti Asuhan Budi Mulia Jember. The program applied participatory and experiential learning approaches through leadership training, value internalization, social mini-project implementation, mentoring, and evaluation. The results indicate improvements in self-leadership, communication skills, teamwork, and social responsibility among participants. The model integrates Islamic leadership values (siddiq, amanah, tabligh, fathanah) with participatory governance principles and social care practices. This program contributes not only to youth empowerment but also to institutional strengthening within social care organizations. The Leadership Smart Social Care model demonstrates potential for replication in similar community-based institutions.